Technique for Seismic Diagnostics of Rock Mass Conditions above the Working in the Course of Mining the Coal Seams Prone to Geodynamic Phenomena - Trifonov, A.; Tumanov, V.; Gluhov, A. (Science and Innovation, 2024)
Methodical guidelines to receive seismic evidence of console block cracking and hardware for continuous recording of seismic processes have been developed. Energy and spectral characteristics of seismic emission for the development of tectonic destruction zones in various rock structures of the upper roof have been established. The ability to display the spatial migration of hypocenters of seismic events and their energy magnitude has been determined. The algorithm for computation of diagnostically informative features of geodynamic hazard has been elaborated.